Identification of Antimicrobial Peptides from the Microalgae Tetraselmis suecica (Kylin) Butcher and Bactericidal Activity Improvement - Fanny Guzmán; Genezareth Wong; Tanya Román; Constanza Cárdenas; Claudio Alvárez; Paulina Schmitt; Fernando Albericio; Verónica Rojas (Marine Drugs, 2019)
The outburst of microbial resistance to antibiotics creates the need for new sources of active compounds for the treatment of pathogenic microorganisms. Marine microalgae are of particular interest in this context because they have developed tolerance and defense strategies to resist the exposure to pathogenic bacteria, viruses, and fungi in the aquatic environment. Although antimicrobial activities have been reported for some microalgae, natural algal bioactive peptides have not been described yet. In this work, acid extracts from the microalga Tetraselmis suecica with antibacterial activity were analyzed, and de novo sequences of peptides were determined. Synthetic peptides and their alanine and lysine analogs allowed identifying key residues and increasing their antibacterial activity. Additionally, it was determined that the localization of positive charges within the peptide sequence influences the secondary structure with tendency to form an alpha helical structure.